PENGARUH PENERAPAN PENDEKATAN METAPHORICAL THINKING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Kristiawati Kristiawati; Baharullah Baharullah; Khairunnisa Abdullah (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
The essence of mathematics is a concept, so learning mathematics requires special ways to learn and teach it.Vision of the development mathematics learning to fill the needs of the present, directing mathematics learning to understanding mathematical concepts / principles which are needed to solve mathematical problems and other scientific problems.However, most of students are still unable to solve mathematical problems because their understanding ability has not developed as they should. Understanding the concept makes it easier for students to solve problems because students will be able to link and solve these problems with provision concepts that are understood.So the approach is needed to improve students' understanding of concept skills. The alternative that  used is to apply the metaphorical thinking approach. This study aims to determine the effect of the metaphorical thinking approach on the students ability  to understand the concepts in Class VIII.3 Islamic Athirah 2 Makassar.the type of this research is a pre-experimental with of The One Group Pretest-Posttest Design. The population in this study were all class VIII at SMP Islamic Athirah 2 Makassar and selected class VIII.3 representing the population.Data collection techniques in this study are tests of concept comprehension ability which are then analyzed with descriptive and inferential statistics using t test. Based on the results of the study, both from the results of analysis or hypothesis testing, it can be concluded that the metaphorical thinking approach affects the ability to understand the concept of students in class VIII at SMP Islamic Athirah 2 Makassar.